Fordele og ulemper ved løbende opdatering af den digitale Retskrivningsordbog - Andersen, Margrethe Heidemann; Jensen, Jørgen Nørby; Jervelund, Anita Ågerup (Nordiske Studier i Leksikografi, 2018)
Once a year, the digital version of Retskrivningsordbogen (the official dictionary of Danish Orthography) is updated with at least 150 new entries. The orthographical rules and the spelling of the existing entries in the dictionary remain unaltered. However, imprecisions in the orthographical system caused by the updating may occur. In this article we describe how we update the dictionary, and we discuss the problems these updates may cause.